An Overview of Advanced Use of Essential Oils for Poultry Health and Disease Management - Larisa Toader; Lavinia Ștef; Aurelia Coroian; Todd Applegate; Igori Balta (Scientific Papers Animal Science and Biotechnologies)
In this review, we discuss how essential oils (EOs) can be used in poultry farming as a sustainable alternative to conventional practices. The study brings to focus the industry’s most urgent issues: antibiotic resistance and improved health, pushing for alternative solutions. Given their antimicrobial, antioxidant and growth promoting capability, EOs are highlighted as potential substitutes with their rich composition of terpenes and phenolics. The review approach how EOs promote poultry health with regard to growth promotion, improving immune function and enhancing feed conversion ratios. It further examines their impact on gut health, disease resistance, and the potential to elevate product quality. The integration of EOs into poultry practices is presented as a strategy to mitigate environmental challenges. We aimed to provide a review of the biological mechanisms behind the efficacy of EOs in managing diseases and promoting health in poultry, against a backdrop of various pathogens.